EXPLORING THE PATHOGENESIS OF RHEUMATOID ARTHRITIS: A REVIEW OF THE EVIDENCE. - 1Abdulelah Almoteri, 2Ahmed Aljohani, 3Adel Alrashidi, EbraheimAlhamawi, 4Abdulrahman Aljohani, 5Adal Alanezi, 6Emad Shiha, 7Ibrahim Alsamiri (Chelonian Research Foundation, 2022)
RA is estimated to affect a significant percentage of the world population. Although the pathophysiology of RA remains unclear, studies suggest that it involves a complex interplay of genetic predisposition, environmental triggers, and dysregulation of the immune system. In this paper, it has conducted an extensive literature review to summarise various RA concepts. it reviewed RA’s pathophysiology by analyzing its pathological immune and inflammatory mechanisms and inter-related processes that lead to tissue damage. Also, discussing the role of autoimmunity in RA, where the body's immune cells mistakenly target healthy tissues, particularly the synovium, leading to chronic inflammation and joint damage. Additionally, we reviewed literature to understand how autoimmunity in RA can be triggered by various factors such as infections, hormonal changes, and environmental exposures. Furthermore, we discussed the genetic component in RA where genetically susceptible individuals, certain alleles, such as HLA-DRB1, are strongly associated with RA development. we described how RA-specific biomarkers such as rheumatoid factor (RF) and anti-cyclic citrullinated peptide antibodies (anti-CCP) aid in diagnosis and monitoring disease progression. We analyzed how pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and interleukin-1 (IL-1) promote synovial inflammation, cartilage degradation, and bone erosion, contributing to joint damage and functional impairment. Finally, we analyzed literature to describe the treatment and management of RA to alleviate symptoms, suppress inflammation, and prevent disease progression. Disease-modifying anti-rheumatic drugs (DMARDs) and biologic agents targeting TNF-α, IL-6, and other inflammatory pathways are the mainstay of RA therapy. Early diagnosis and aggressive treatment strategies, including combination therapies and treat-to-target approaches, have been shown to improve outcomes and prevent long-term joint damage. Regardless of RA’s complex nature, advances in understanding RA pathophysiology, biomarkers, and treatment strategies have improved clinical outcomes and quality of life for affected individuals. Keywords: Rheumatoid Arthritis, Autoimmunity, Synovium, Inflammation, Joint damage, Genetic predisposition, Environmental triggers, Biomarkers, Rheumatoid Factor, Anti-cyclic citrullinated peptide antibodies, Pro-inflammatory cytokines, Disease-modifying anti-rheumatic drugs (DMARDs), Biologic agents, Treat-to-target approach, Functional impairment.